PENGARUH PROFITABILITAS AKTIVITAS DAN LIKUIDITAS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN TEKSTIL DAN GARMENT DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Umi Mas’ulah; Iip Dyah Kusumaningati; Revyta Wulandari (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
Profit growth shows that the financial condition of a company is good from a financial perspective. The company's profits are expected to increase every year in order to support the sustainability of the company's business in competing. This research was conducted with the aim of determining the influence of profitability, activity and liquidity on profit growth in the textile and garment sector listed on the Indonesia Stock Exchange in 2018-2022. The results of this research show that Profitability partially has a significant effect on Profit Growth, this is proven based on its significance value, namely 0.308 > 0.05. Partial activity has a significant effect on Profit Growth, this is proven based on the significance value, namely 0.345 > 0.05. Liquidity partially has a significant effect on Profit Growth, this is proven based on its significance value, namely 0.838 > 0.05. The conclusion is that the influence of the Profitability Ratio has a negative effect which is not significant, the Activity Ratio has a negative effect which is not significant and the Liquidity Ratio has a negative effect which is not significant.